Supercritical fluid chromatography coupled to high-resolution tandem mass spectrometry: an innovative one-run method for the comprehensive assessment of chocolate quality and authenticity - Rektorisova, Michaela; Hrbek, Vojtech; Tomaniova, Monika; Cuhra, Petr; Hajslova, Jana (Analytical and bioanalytical chemistry, 2022)
To assess chocolate quality and authenticity comprehensively, a combination of various analytical procedures is involved, thereby making the process time-consuming and costly. Thus, we investigated the potential of ultra-high performance supercritical fluid chromatography coupled to quadrupole-time of flight mass spectrometry (UHPSFC-QTOF-MS) as an alternative to "classic" methods. By combining hexane and aqueous extracts from sequential extraction, a single 8-min analytical run enabled us (i) to determine cocoa butter equivalents (CBEs) and milk fat content based on the detection of selected triacylglycerols, (ii) to calculate dry non-fat cocoa solids based on determined theobromine and caffeine content, and (iii) to profile contained sugars. To obtain the most comprehensive information about sample composition, the MS method comprised a full MS scan for non-target screening and several time-scheduled targeted MS/MS functions ("parallel reaction monitoring") optimized according to the possible concentration ranges of the analytes. For 40 different chocolate samples, our results and those obtained by using standard methods (LC-UV for non-fat cocoa solids, and GC-FID for CBEs) were in good agreement. Compared to the conventional approach for chocolate quality and authenticity control, the presented SFC-MS method is a fast, cost-effective, and efficient alternative, and only samples suspicious for the presence of CBE should be referred to the standard GC-FID method for exact CBE quantification. In the study, also some challenges offered by SFC-MS have been addressed.
Keywords: čokoláda; Chromatography, Supercritical Fluid; Gas Chromatography-Mass Spectrometry; UPC2; kakaovník; superkritická fluidní chromatografie; Cocoa butter equivalents; Chocolate; SFC-HRMS; Sugars; Theobromine; Triacylglycerols; tandemová hmotnostní spektrometrie; Cacao; plynová chromatografie s hmotnostně spektrometrickou detekcí; Tandem Mass Spectrometry